2018
DOI: 10.1007/s00234-018-2135-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations of hemodynamics, morphology, and patient characteristics with aneurysm rupture stratified by aneurysm location

Abstract: Purpose-The mechanisms of cerebral aneurysm rupture are not fully understood. We analyzed the associations of hemodynamics, morphology, patient age and gender with aneurysm rupture stratifying by location.Methods-Using image-based models, 20 hemodynamic and 17 morphological parameters were compared in 1931 ruptured and unruptured aneurysms with univariate logistic regression. Rupture rates were compared between males and females as well as younger and older patients and bifurcation versus sidewall aneurysms fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 33 publications
2
45
0
2
Order By: Relevance
“…When such data become available for AAA, the link between 'high risk' as defined here by clinicians and rupture prediction should be studied. A very recent study in cerebral aneurysms showed adverse morphology and hemodynamics to be related to aneurysm rupture 22 . The corresponding statistical model of rupture probability was then successfully validated 23 .…”
Section: Limitationmentioning
confidence: 99%
“…When such data become available for AAA, the link between 'high risk' as defined here by clinicians and rupture prediction should be studied. A very recent study in cerebral aneurysms showed adverse morphology and hemodynamics to be related to aneurysm rupture 22 . The corresponding statistical model of rupture probability was then successfully validated 23 .…”
Section: Limitationmentioning
confidence: 99%
“…The first set of exclusion criteria were as follows: (a) CFD-unrelated (n = 5), (b) rupture-point-known (n = 10), (c) discriminator-unrelated (n = 26), (d) small number of aneurysms (less than 30) (n = 28), and (e) WSS or OSI undisclosed (n = 11), yielding a total of 32 studies. The second set of exclusion criteria were as follows: (f) location-specific (n = 14), (g) locationundefined (n = 2), (h) size-restricted (n = 1), and (i) metaanalysis (n = 2), yielding a total of 13 studies [38,39,[45][46][47][48][49][50][51][52][53][54][55]. Setting a specific location and size was avoided since those factors are known to be related to the aneurysm rupture rate and may lead to a possible bias; however, casematching studies based on location and size were permitted.…”
Section: Study Selectionmentioning
confidence: 99%
“…From the 13 included studies [38,39,[45][46][47][48][49][50][51][52][53][54][55], the following data were extracted: (1) year of publication, (2) study design, (3) location of aneurysms, (4) number of aneurysms, (5) number of ruptured aneurysms, (6) aneurysmal size, (7) aneurysmal aspect ratio, (8) aneurysmal WSS, (9) aneurysmal normalized WSS (NWSS), (10) aneurysmal OSI, and (11) aneurysmal LSA%. The mean (or median), p value, and area under the curve (AUC) from a receiver operating characteristic (ROC) analysis of these geometric and hemodynamic indexes were extracted.…”
Section: Data Extraction and Processingmentioning
confidence: 99%
See 2 more Smart Citations